The Relationship Between Mother's Knowledge And Attitude With Behavior Prevention Of Ari In Toddlers In Work Areas Telaga Dewa Public Health Center, Bengkulu City Year 2025 - Palingga, Imelda; Wulandari, Wulandari; Aprianti , Delta (Utami Publisher, 2025)
ISPA has significant global health impact and need become focus attention in effort prevention And disease control . WHO data (2020) reports that in know ISPA In toddlers aged 1-5 years there were 1,988 cases with a prevalence of 42.91%, Indonesian data increased to 2,312 cases in 2022. The aim of the study was to see the relationship between maternal knowledge and attitudes with ISPA prevention behavior in toddlers in the Telaga Dewa Community Health Center work area.simple random sampling techniques and obtained a sample size of 72 respondents. Data collection was conducted using a questionnaire on knowledge, attitudes, and behaviors regarding ARI prevention. Based on the results of univariate analysis, it is known that a small portion of respondents had good knowledge, namely 36.1%, Most of the respondents had positive attitudes, namely 62.5% and positive behavior, namely 73.6%. Bivariate analysis showed a p value <0.014, namely 0.001, which means there is a significant relationship between maternal knowledge and maternal attitudes with ISPA prevention behavior in toddlers in the work area of the Telaga Dewa Bengkulu Community Health Center. Researchers suggest that for nursing services, the research results can be used as a basis for designing more effective educational and intervention programs to improve mothers' knowledge and attitudes regarding the prevention of ARI in toddlers.